Adaptación de prótesis ocular en ojo derecho en paciente de 53 años. - Martínez Aumala, María José (2022)
An ocular prosthesis allows correcting at an esthetic level the loss of the eye, substituting the lack of the eyeball and providing a solution of well-being and advantage in the patient's quality of life. The present is a clinical case that shows the adaptation of ocular prosthesis in a 53-year-old patient, who presents extirpation in right eye by surgical intervention of enucleation for showing a diagnosis of malignant conjunctival melanoma of epitheliode type, same that threatened the patient's life. After two months, the postoperative control progress is normal, with good local healing at the level of the parpebral conjunctiva. Once the optimal state of the cavity was verified, we proceeded to determine the size of the prosthesis mold using the visualization system, placing PMMA (polymethylmethacrylate) material conformers to fix the mold of the cavity and consecutively replace them and adapt the ocular prosthesis of the same material, which guarantees biocompatibility and confidence to the patient, improving his quality of life. The prosthesis fitting process was carried out in six sessions: from the initial interview with the patient to the evaluation in the last stage, which yielded the expected results of comfort and esthetic solution. Among the recommendations, we proceeded to provide indications to avoid future discomfort, such as the following of hygiene rules, the instruction to correctly place and remove the prosthesis; it is also suggested to use frame lenses to protect and achieve greater naturalness of vision.